2022
DOI: 10.1038/s41598-022-14083-3
|View full text |Cite
|
Sign up to set email alerts
|

Ceramides are early responders in metabolic syndrome development in rhesus monkeys

Abstract: Metabolic syndrome increases risk of complicating co-morbidities. Current clinical indicators reflect established metabolic impairment, preventing earlier intervention strategies. Here we show that circulating sphingolipids are altered in the very early stages of insulin resistance development. The study involved 16 paired overweight but healthy monkeys, one-half of which spontaneously developed metabolic syndrome over the course of 2 years. Importantly, animals did not differ in adiposity and were euglycemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Regarding the clinical research area, a recent study involving overweight but healthy monkeys showed a strong correlation between ceramides and the onset of early-stage metabolic syndrome symptoms, highlighting the relevance of circulating ceramides in identifying risk between healthy and impaired study groups. This highlights the potential of ceramides as a simple and minimally invasive diagnostic tool for metabolic syndrome ( Smith et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the clinical research area, a recent study involving overweight but healthy monkeys showed a strong correlation between ceramides and the onset of early-stage metabolic syndrome symptoms, highlighting the relevance of circulating ceramides in identifying risk between healthy and impaired study groups. This highlights the potential of ceramides as a simple and minimally invasive diagnostic tool for metabolic syndrome ( Smith et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…Over several years, it proceeds to necrosis of beta cells, a sharp drop in insulin levels, and hyperglycemia. 59,123,124 The Zebrafish model is an attractive model system for the study of metabolic abnormalities. Zebrafish have preserved energy balance and cholesterol metabolism.…”
Section: Non-rodent Models For Type 2 Diabetic Animal Modelsmentioning
confidence: 99%
“…If kept on an ad libitum laboratory diet, especially fructose, it develops obesity, hyperinsulinemia, and insulin resistance. Over several years, it proceeds to necrosis of beta cells, a sharp drop in insulin levels, and hyperglycemia 59,123,124 …”
Section: Animal Models For Diabetic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the four SMs were negative, while the above Cers were positively correlated with TC, TG, LDL-C, ALT, and AST. An abundance of evidence has demonstrated the contribution of Cers and SMs to metabolic disorders and cardiovascular diseases [47,48]. What's more, the chain lengths, number of double bonds, and number of hydroxyls on the sphingoid base and fatty acid residue impact the biological activities of Cers and SMs [49,50].…”
Section: Ceramides and Smsmentioning
confidence: 99%